Desain Penelitian Teks (Naskah) - Muhammad Naufal Baehaki; Dina Hermina; Salamah (PT. Hasba Edukasi Mandiri, 2026)
Text research design constitutes a systematic framework used to investigate written documents, manuscripts, literary works, historical records, and digital texts. This study aims to examine the conceptual foundations, methodological approaches, and practical implementation of text-based research in qualitative studies. The research employed a descriptive qualitative approach through a literature review method based on the framework proposed by Creswell. Data were collected from books, scientific journals, research reports, and relevant academic documents discussing text analysis, discourse analysis, corpus linguistics, and qualitative methodology. The findings indicate that text research design has evolved from traditional philological and hermeneutic approaches into more contemporary models such as content analysis, discourse analysis, corpus analysis, and narrative analysis. Furthermore, technological advancements have significantly expanded opportunities for text-based research through digital corpora and analytical software. A well-structured research design contributes to the validity, reliability, and scientific rigor of qualitative inquiry.